Variable speed control of DC motor using four quadrant controlled rectifier based on Human Machine Interface - Muhammad, Razi; Yuhendri, Muldi (Department of Electrical Engineering Universitas Negeri Padang, 2024)
Various industrial equipment uses dc motors as its drive. In order for the dc motor to operate as needed, it needs to be controlled. Some of the controls applied to dc motors include control of rotation direction, speed, braking, and starting current starting. This paper proposes controlling the speed of the dc motor using a 4-quadrant controlled rectifier or phase controller using a programmable logic controller (PLC) and human machine interface (HMI) as the control center. The system design is implemented on a 1.3 HP separate amplifier dc motor. The proposed control system design is tested and validated at varying speeds. Variations in motor speed are set on the HMI screen according to needs. The test results show that the design of the dc motor speed control system using a four quadran phase controller has worked as desired. The speed of the motor can be controlled through the HMI display